The Location of New Kingdom Elite Tombs – Space, Place and Significance - Johannes Stefan G. Auenmüller (Ksiegarnia Akademicka Publishing, 2014)
This paper deals with the significance of provincial New Kingdom elite tomb location. It aims to describe a key element of the relationship between the elite and the spatial distribution of their archaeological evidence in terms of ‘territoriality’. It focuses especially on the tomb, the pivotal component of the elite’s monumental display. A unique perspective is adopted, derived from both the sociology of space and cultural anthropology. The theoretical background of ‘territoriality’ and its wide range of applications are outlined firstly with a short review of key definitions. The paper’s focus then shifts to the domain of funerary archaeology by examining the location of tombs and its significance. The factors affecting location are discussed from a prosopographical perspective and contrasted with statements from so-called (auto-)biographical self-presentations. Both inscriptional and prosopographical data is the key to understand the underlying considerations for tomb location.